National survey of the injury prevention activities of sure start children's centres. (1st March 2011) - Watson, M C; Kendrick, D; Stewart, J; Coupland, C; Hayes, M; Wynn, P
Abstract : Objectives: To explore the injury prevention activity being undertaken by Children's Centres. Background: Sure Start Children's Centres are an important part of the UK Governments 10-year childcare strategy. The aim of the Centres is to improve health outcomes for all children. Accident prevention is one of the many vital roles Sure Start Children's Centres have in protecting and promoting the health of children. The Centres have the potential to make significant contributions to home safety for children under 5. Methods: A national postal survey will be undertaken in England to ascertain what activities Children's Centres are undertaking to prevent accidental injuries. The study population will comprise managers of Children's Centres. Cluster sampling will be used and 600 Centres will be included in the sample. Results: The results will include: characteristics of Centres; Children's Centres health priority areas; injury prevention activity; knowledge and attitudes towards injuries and their prevention; and, barriers and facilitators to injury prevention activity. In addition, the data will provide an insight into accident prevention partnerships in England, from a Children's Centre perspective. Conclusion: The findings will show what accident prevention activities for the under 5s are currently provided by Children's Centres across the country; and what support is needed to help Children Centre staff prevent accidents in the home. The study may highlight barriers to action as well as innovative effective practice.